Peranan Ulama Dalam Perang Aceh Tahun 1873-1912 - Febri Setiawan; Hanafiah Hanfiah; Reni Nuryanti (Program Studi Pendidikan Sejarah - Universitas Samudra, 2023)
The Acehnese war against the Dutch in 1873-1912, the resistance of the Acehnese sultanate to the ulama, is historically sociological in that the roles of ulama and umara cannot be separated in the life of the Acehnese people, where they both have an influence on the social life of the Acehnese people, so they have a special position between the two. The aims of this research are: (1) to find out the historical background to the emergence of ulama during the Aceh war of 1873-1912 (2) to find out the role of ulama in the Aceh war of 1873-1912. This research uses a type of historical research method with a library research approach, data collection techniques using materials related to research originating from scientific journals, literature and library study authors, data analysis techniques to describe and interpret the data obtained appropriately. needs that include data display and verification. The results of this research are that (1) the background to the emergence of ulama during the Aceh war of 1873-1912 was caused by four factors, namely political factors, religious factors, cultural factors, social factors and the war against the Dutch. (2) the role of the ulama in 1873-1912 was to increase the enthusiasm of the Acehnese people in implementing Islamic law.